(untitled) (VERUM: Journal of Scientific Initiation, 2025)
This paper, which is dedicated to the theme of educational policies, aims to reflect on the influence of neoliberalism on education, especially in the Basic Education Curriculum Plan of Mozambique. From a methodological point of view, the work was guided by a qualitative approach based on a bibliographic review, documentary research and content analysis. Through the policy cycle approach, in the contexts of practice and effects, it was possible to verify that educational policy in Mozambique is influenced by international organizations that exercise power in its design, enabling the elaboration of curricular reforms that do not satisfy the contextual reality of the country. Furthermore, the Basic Education Curriculum Plan presents a perspective of technical training that fits into the neoliberal agenda aimed at capacitation for the labor market.